PERSIAPAN PEMBELAJARAN PENDIDIKAN JASMANI ADAPTIF SISWA SDLB NEGERI 40 KABUPATEN SOLOK - Nia Purnama Sari (STKIP ROKANIA, 2016)
The research problem is planning of the adaptive physical education learning for students with special needs at SDLB Negeri 40 Kabupaten Solok has not been implemented as expected. Form of this research was used descriptive qualitative with direct observation and unstructured interview method. The key informan of this research is the head master and another informan are teachers and students with special needs. Analysis of data using qualitative analysis techniques. Based on the result of a series observations and interviews, show the result that planning of the adaptive physical education learning is not appropriate curriculum and teachers whose teaching is not sport educatian teacher